2019
DOI: 10.1002/anie.201814265
|View full text |Cite
|
Sign up to set email alerts
|

ZnSe Nanorods as Visible‐Light Absorbers for Photocatalytic and Photoelectrochemical H2 Evolution in Water

Abstract: A precious‐metal‐ and Cd‐free photocatalyst system for efficient H 2 evolution from aqueous protons with a performance comparable to Cd‐based quantum dots is presented. Rod‐shaped ZnSe nanocrystals (nanorods, NRs) with a Ni(BF 4 ) 2 co‐catalyst suspended in aqueous ascorbic acid evolve H 2 with an activity up to 54±2 mmol g ZnSe −1 h −1 and a quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 67 publications
1
70
0
Order By: Relevance
“…These merits make them potential supplements or alternatives to the Cd‐based materials in photocatalytic hydrogen generation and biomedical applications . Recent research on ZnSe and alloyed ZnS x Se 1− x NRs indicated that these Cd‐free NRs can be adopted as efficient photocatalysts for efficient hydrogen generation and oxygen evolution reactions …”
Section: Introductionmentioning
confidence: 99%
“…These merits make them potential supplements or alternatives to the Cd‐based materials in photocatalytic hydrogen generation and biomedical applications . Recent research on ZnSe and alloyed ZnS x Se 1− x NRs indicated that these Cd‐free NRs can be adopted as efficient photocatalysts for efficient hydrogen generation and oxygen evolution reactions …”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that ZnSSe alloyed nanorods showed increased oxygen evolution reaction (OER) activity compared with pure ZnSe and ZnS nanorods (Figure a) because the alloyed nanorods have reduced energy barrier for oxygen evolution . Following from this work, ZnSe nanorods was applied as the visible light range absorbers for H 2 evolution with performances exceeding those of Cd‐containing QDs …”
Section: Photoelectronic Energy Conversion Applicationsmentioning
confidence: 76%
“…Previously reported ZnSe NRs all had the hexagonal WZ crystal structure, with the initially formed ZnSe clusters being able to attach along their c axes or to individually grow along the c axis to form 1D ZnSe NCs . Herein, we have obtained ZnSe NRs with the ZB crystal structure for the first time, and thus we conducted further experiments in an effort to understand their formation mechanism.…”
Section: Figurementioning
confidence: 94%
“…Some examples of ZnSe NRs have been reported previously, but in far less an extent than for the Cd‐based NRs. Most of the synthetic routes to form ZnSe NRs used the oriented attachment method, wherein small non‐anisotropic ZnSe clusters attached to each other to form ZnSe NRs with or without the use of confining or directing organic templates . To the best of our knowledge, all of the reported ZnSe NRs produced by this or other methods exhibited the hexagonal wurtzite (WZ) crystal structure, even when their synthesis started from ZnSe clusters with a cubic zinc blende (ZB) crystal structure .…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation